Should treatment of hypogammaglobulinemia with immunoglobulin replacement therapy (IgRT) become standard of care in patients with chronic lymphocytic leukemia? - Noto, Alessandro; Cassin, Ramona; Mattiello, Veronica; Bortolotti, Marta; Reda, Gianluigi; Barcellini, Wilma (Frontiers in Immunology, 2023)
Hypogammaglobulinemia (HGG) is a frequent finding in patients with hematological malignancies, and is commonly described in chronic lymphocytic leukemia (CLL) before or after treatment. We reviewed published literature available online in the last thirty years through Medline search of indexed articles focusing on the main differences and advantages of the products now available on the market, namely intravenous Ig (IVIg) and subcutaneous Ig (SCIg) preparations. IgRT is effective and safe in the prophylaxis of infections in a selected group of patients with CLL and hypogammaglobulinemia and is therefore a valuable tool for clinicians in the everyday management of infectious risk. We encourage the use of SCIg formulations as they appear to have similar efficacy but better cost-effectiveness and tolerability.